The Sexual Deviations of the Main Character in the Novel Sang Guru Piano by Elfriede Jelinek (A Study in Psychology Literature) - Kastanja, Reiverd Novian; Maspaitella, Martha; Latupapua, Falantino Eryk (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Humans serve as subjects in literary works as they embody behaviors observable via the lens of their experiences. Behavior constitutes a facet of the soul's conflict, as psychological disorders manifest through human conduct, each exhibiting distinct characteristics. Human beings can be examined through science, particularly psychology, which pertains to the psyche. Consequently, literary works are seen as a psychological phenomenon. Literary works, stemming from the author's endeavors, are frequently linked to psychological phenomena, as they represent the author's creation, whereby psychological theory is employed both intentionally and unconsciously.